2012
DOI: 10.3109/10929088.2012.744096
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted planning and navigation improves cutting accuracy during simulated bone tumor surgery of the pelvis

Abstract: Background: Resection of bone tumors within the pelvis requires good cutting accuracy to achieve satisfactory safe margins. Manually controlled bone cutting can result in serious errors, especially due to the complex three-dimensional geometry, limited visibility, and restricted working space of the pelvic bone. This experimental study investigated cutting accuracy during navigated and non-navigated simulated bone tumor cutting in the pelvis. Methods: A periacetabular tumor resection was simulated using a pelv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 34 publications
1
39
0
1
Order By: Relevance
“…The result concurred with the accuracy of the two techniques reported in other clinical, sawbone or cadaveric studies [5,11,19,[22][23][24]. When we compared the accuracy between the two techniques in simulated pelvic bone resections, no statistical difference was noted.…”
Section: Discussionsupporting
confidence: 92%
“…The result concurred with the accuracy of the two techniques reported in other clinical, sawbone or cadaveric studies [5,11,19,[22][23][24]. When we compared the accuracy between the two techniques in simulated pelvic bone resections, no statistical difference was noted.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies on preoperative 3D surgical simulation planning used simulation results to prepare a surgical guide for application in the actual surgery. [3,4] Studies showed that, when the 3D surgical simulation planning was performed, the error between the bony segments could be decreased for mandibular reconstructions with the fibula. [5,6] When the mandibular reconstruction with the fibula was performed in patient groups with or without advance 3D surgical simulation planning for the plating, the results showed no significant difference between groups in the midline deviation; however, with advance simulation planned plating, less error was observed in the deviation at the condylar position, and the errors were partially reduced in the mandible body axis and the angular shift.…”
Section: Discussionmentioning
confidence: 99%
“…8). An osteosarcoma in the pelvis is an example in which computer-assisted surgery will help navigate precise bone cuts due to the complex three-dimensional anatomy and preserve critical structures [104][105][106].…”
Section: Surgical Treatmentmentioning
confidence: 99%